Experimental Study on the Emission Performance of Lean Premixed Bunsen Flame with Piloted Rich Premixed Flame. Issue 1 (1st January 2022) - Cui, Yongzhang; Zhang, Lili; Yu, Chang; Yin, Pengfei; Liu, Yiming
Abstract: Lean premixed flame has lower nitrogen oxide emission for lower flame temperature. Whereas its poor flame stability, an annual rich pilot premixed flame was used to enhance flame stability and reduce emissions with lower ratio of pilot flame and main lean flame load. With the increasing of pilot flame load, air coefficient of main flame increases gradually. Increasing the main flame load, the air coefficient of stable main flame decreases, while the nitrogen oxide and carbon monoxide changes little. Under all main flame load, nitrogen oxide and carbon monoxide decrease sharply at first and then gets slowly. The ultralow Nitrogen Oxide of 18 mg/m³and carbon monoxide of 50 mg/m³can be reached, under the condition of main flame air coefficient from 1.3 to 1.5.